An analysis of patterns and predictors of self-reported common mental disorders in Ibadan Metropolis, Nigeria - Adeniyi Sunday Gbadegesin; Godwin O. Ikwuyatum (Journal of Community Safety and Well-Being)
Common mental disorders (CMDs) have been on the rise in developing countries. This study set out to unravel the pattern of CMD prevalence in a traditional African city, Ibadan. The study, in addition to socio-economic and demographic variables, takes into cognisance the effect of some peculiar environmental variables. The Self-Reporting Questionnaire-20 was used for CMD screening, and the questionnaire was administered to 1,200 respondents in a cross-sectional survey approach. The results showed that the overall pattern of CMD prevalence is random (Global Moran’s I (P = 0.78, I = 0.00 and Z = 0.29)). Respondents without education reported the highest cases of CMD (48.6%). When combined together, migrants reported 52.5% of the CMDs. The significant variables are food security (β = −0.198), green space (β = −0.057), migration status (β = −0.054), flood-prone residence (β = 0.453), low-quality housing (β = −0.061), frequent recreation participation (β = −0.071), experience of spousal violence (β = 0.199), positive self-rated health (β = −0.134) and positive quality of life (β = −0.205). The predictors of CMD explained about 35.8% of the variation (R2) and an R value of 59.9%. The study showed that CMDs occur among most of the urban population. Adequate media sensitization will have significant ameliorating effects on urban residents.